Emotion regulation, brain behavioural systems, and sensory sensitivity in sociocultural attitudes towards appearance in adolescents - Amiri, Sohrab; Navab, Amir Ghasemi (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2019)
This study investigates the usefulness of the emotion regulation (ER) brain behavioural systems and sensory sensitivity to better understand sociocultural attitudes towards appearance. Specifically, associations between positive and negative ER, and incremental validity of brain behavioural systems and highly sensitive person (HSP) as predictors of the attitudes towards appearance are examined. Data were obtained in a sample of healthy adolescents (N = 331). Results of a series of multiple regression analyses showed that ER provided a significant prediction of each of the five attitudes towards appearance variables. Dimensions of brain behavioural systems including behavioural activation system (BAS), behavioural inhibition system (BIS), fight-flight-freeze system (FFFS) showed multiple associations with facets from the attitudes towards appearance. BAS and FFFS were found to be the positive predictors and BIS was a negative predictor. HSP was found to be a positive predictor of attitudes towards appearance. The results expand the understanding of the attitudes towards appearance and indicate how domains of ER, personality, and sensory processing could explain the attitude of adolescents towards their appearance.